Dissecting EPPIN protease inhibitor domains in sperm motility and fertilizing ability: Repercussions for male contraceptive development - Silva, Alan A. S [UNESP]; Raimundo, Tamiris R. F [UNESP]; Mariani, Noemia A. P [UNESP]; Kushima, Hélio [UNESP]; Avellar, Maria Christina W; Buffone, Mariano G; Paula-Lopes, Fabíola F; Moura, Marcelo T; Silva, Erick J. R [UNESP] (Oxford University Press (OUP), 2021)
EPPIN (epididymal protease inhibitor) is a mammalian conserved sperm-binding protein displaying an N-terminal WFDC (whey-acidic protein four-disulfide core) and a C-terminal Kunitz protease inhibitor domains. EPPIN plays a key role in regulating sperm motility after ejaculation via interaction with the seminal plasma protein SEMG1 (semenogelin-1). EPPIN ligands targeting the SEMG1 binding site in the Kunitz domain are under development as male contraceptive drugs. Nevertheless, the relative contributions of EPPIN WFDC and Kunitz domains to sperm function remain obscure. Here, we evaluated the effects of antibodies targeting specific epitopes in EPPIN's WFDC (Q20E antibody, Gln20-Glu39 epitope) and Kunitz (S21C and F21C antibodies, Ser103-Cys123 and Phe90-C110 epitopes, respectively) domains on mouse sperm motility and fertilizing ability. Computer-assisted sperm analysis showed that sperm co-incubation with S21C antibody (but not F21C antibody) lowered progressive and hyperactivated motilities and impaired kinematic parameters describing progressive (straight-line velocity; VSL, average path velocity; VAP and straightness; STR) and vigorous sperm movements (curvilinear velocity; VCL, amplitude of lateral head movement; ALH, and linearity; LIN) compared with control. Conversely, Q20E antibody-induced milder inhibition of progressive motility and kinematic parameters (VAP, VCL and ALH). Sperm co-incubation with S21C or Q20E antibodies affected in vitro fertilization as revealed by reduced cleavage rates, albeit without changes in capacitation-induced tyrosine phosphorylation. In conclusion, we show that targeting specific epitopes in EPPIN Kunitz and WFDC domains inhibits sperm motility and capacitation-associated events, which decrease their fertilizing ability; nevertheless, similar observations in vivo remain to be demonstrated. Simultaneously targeting residues in S21C and Q20E epitopes is a promising approach for the rational design of EPPIN-based ligands with spermostatic activity.
Keywords: Capacitation; Drug target; Fertilization; Hyperactivation; Male contraception; Sperm motility; Spermatozoon